Factors associated with long COVID at a pandemic hospital in Turkey: a prospective observational study with 3-month follow-up - Akbaba Bağcı, Belma; Satıcı, Celal (The Journal of Infection in Developing Countries, 2025)
Introduction: The aim of this study was to evaluate the course of the coronavirus disease 2019 (COVID-19) symptoms and identify the prognostic factors in patients who continued to have symptoms for ≥ 3 months. The occurrence of symptoms was compared based on gender. Methodology: This was a prospective cohort study performed at a tertiary chest hospital in Turkey. The clinical features of patients with COVID-19, health anxiety scores, and the course of symptoms at admission and follow-up were compared based on gender. The primary outcome was the distribution and rate of persistent symptoms at the third month; and the secondary outcomes were the number and distribution of symptoms by gender, and the relationship between symptoms and health anxiety. Results: A total of 110 patients (mean age of 45 years) were followed. Of these, 53 (48%) patients were females. Forty-seven (43%) patients, including 17 (32%) females, were hospitalized. The number of highly symptomatic patients with mild disease severity (level 2) was significantly higher among females than males (p = 0.008). Eighty-one (74%) patients followed had at least 1 symptom persisting at the end of the third month. During the 3-month follow-up, the total number of symptoms and health anxiety scale scores were significantly higher in females (p = 0.04 and p = 0.004, respectively), especially in females aged < 50 years (p = 0.005). Conclusions: Thus, persistent symptoms remained at a high rate at 3 months post-COVID; and gender and neuro-psychiatric factors should be discussed in the etiology of long COVID.